Continuance intention and digital health resources from the perspective of elaboration likelihood model and DART model: a structural equation modeling analysis - Fei, Chengcheng; Zhou, Haixia; Wu, Wei; Jiang, Longyuan; Xu, Yuanqi; Yu, Haiyan (Frontiers in Public Health, 2024)
Background: Internet hospitals, online health communities, and other digital health APPs have brought many changes to people's lives. However, digital health resources are experiencing low continuance intention due to many factors, including information security, service quality, and personal characteristics of users. Methods: We used cross-sectional surveys and structural equation modeling analysis to explore factors influencing user willingness to continue using digital health resources. Results: Information quality (β = 0.31, P < 0.05), service quality (β = 0.19, P < 0.05), platform reputation (β = 0.34, P < 0.05), and emotional support (β = 0.23, P < 0.05) have significant positive effects on user value co-creation behavior. Additionally, user trust and perceived usefulness could mediate the association between user value co-creation behavior and continuance intention, with mediation effects of 0.143 and 0.125, respectively. User involvement can positively moderate the association between user value co-creation behavior and user trust (β = 0.151, t = 2.480, P < 0.001). Also, user involvement can positively moderate the association between value co-creation behavior and perceived usefulness (β = 0.103, t = 3.377, P < 0.001).The keys to solving the problem of low continuance intention are improving the quality and service level of digital health resources, and promoting users' value co-creation behavior. Meanwhile, enterprises should build a good reputation, create a positive communication atmosphere in the community, and enhance user participation and sense of belonging.